1960
DOI: 10.1103/physrev.120.158
|View full text |Cite
|
Sign up to set email alerts
|

Decay ofPm149(53 hr)

Abstract: The radioactive sources were obtained from neodymium oxide, enriched in Nd 148 , irradiated in the Argonne reactor CP-5. After the 1.8-hr activity of Nd 149 had decayed away, the 53-hr activity in 6iPni 149 remained. Some of the samples were purified by ion-exchange-column techniques before being studied. The radiations were investigated with a 180° focusing beta-ray spectrometer and the Argonne 256-channel scintillation coincidence spectrometer. The magnetic spectrometer resolved two components of the beta sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1961
1961
1978
1978

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The 53 hour activity of 149pm has been investigated previously by several groups [1][2][3][4][5][6][7]. The 53 hour activity of 149pm has been investigated previously by several groups [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 53 hour activity of 149pm has been investigated previously by several groups [1][2][3][4][5][6][7]. The 53 hour activity of 149pm has been investigated previously by several groups [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The 53 hour activity of 149pm has been investigated previously by several groups [1][2][3][4][5][6][7]. Artna et al [3] and Schmid et al [4] independently and simultaneously did beta-gamma coincidences by using long lens magnetic spectrometer and 180 ~ beta ray spectrometer respectively. However, found that the decay consisted of only a single beta group of end-point 1050keV leading to the ground state of 1498m.…”
Section: Introductionmentioning
confidence: 99%